Chitosan/polyvinyl alcohol/thiabendazoluim-montmorillonite bio-nanocomposite films: Mechanical, morphological and antimicrobial properties. (1st September 2019) - Bourakadi, Khadija El; Merghoub, Nawal; Fardioui, Meriem; Mekhzoum, Mohamed El Mehdi; Kadmiri, Issam Meftah; Essassi, El Mokhtar; Qaiss, Abou el Kacem; Bouhfid, Rachid
Abstract: Recently, the development of biopolymer/organoclay nanocomposites for food packaging, where at least one of the components is derived from nature or even biomass, has attracted much attention since the properties of polymers can be enhanced and controlled by nanotechnology. In this context, four thiabendazolium surfactants have been synthesized, characterized and used for the organo-modification of sodium montmorillonite (Ms) through cationic exchange procedure. The resulting thiabendazolium-montmorillonite (Mt) exhibits a large d -spacing from 1.17 nm to 1.87 nm between silicate layers. Mt at fixed content (5 wt%) was incorporated in chitosan/Polyvinyl alcohol (CS/PVA) matrix using casting method to produce a new bio-composite films based on chitosan/Polyvinyl alcohol (CS/PVA) and modified thiabendazolium-montmorillonite (Mt). The microstructure and the morphology of these bio-composites were studied by Fourier-transform infrared spectroscopy (FTIR) and scanning electronic microscopy (SEM). The morphological characterization in the bio-composites, show a better dispersion/distribution of Mt and a strong interaction with the polymer chains, these results can be enhanced the mechanical properties of the new bio-films in term of Young's modulus, tensile strength (from 66.98 to 143.43 MPa and from 24.95 to 34.65 MPa, respectively). Further, the antimicrobial test proved the new films to have a good antimicrobial activities against all the bacterium taken for the test (aeruginosa, S. aureus and E. coli) compared to the neat film (CS/PVA). From the results, it is clear that the composite-films have the potential for possible utilization in active packaging applications.